Assessment of Design Procedures for Vertical Borehole Heat Exchangers - Sailer,E; Taborda,DMG; Keirstead,J (2015)
The use of ground source energy systems is a well-established method to provide low cost heating to buildings, diversify the energy mix and help meeting increasingly stricter sustainability targets. However, considerable uncertainties remain over their efficient design, with several standards, guidelines and manuals being proposed over the last few years. This paper aims at providing insight into the implications to the design of a vertical borehole heat exchanger of the adoption of different design procedures. The hypothetical case of a typical dwelling located in London, UK, is analysed in order to highlight the impact on the final design of the chosen methodology. Moreover, a parametric study using an analytical design procedure was performed to point out the influence of various factors, such as borehole characteristics and thermal properties of the ground. It is shown that there are considerable discrepancies between design methods and that uncertainties in some input parameters, such as the thermal properties of the ground, which for relatively small systems are often selected from tables rather than measured in situ, may have a substantial influence on the length of borehole required.